Why nanoprojectiles work differently than macroimpactors: The role of plastic flow - Anders, Christian (2012)
Atomistic simulation data on crater formation due to the hypervelocity impact of nanoprojectiles of up to 55 nm diameter and with targets containing up to 10^10 atoms are compared to available experimental data on micron-, mm-, and cm-sized projectiles. We show that previous scaling laws do not hold in the nanoregime and outline the reasons: within our simulations we observe that the cratering mechanism changes, going from the smallest to the largest simulated scales, from an evaporative regime to a regime where melt and plastic flow dominate, as is expected in larger microscale experiments. The importance of the strain-rate dependence of strength and of dislocation production and motion are discussed.